(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
In the article, one of the most urgent problems of the present day, such as determining ways to strengthen the work motivation of employees in the enterprise, developing employees, taking into account their professional and skill structure, determining their general and additional needs, orienting employees to achieve a specific goal, as well as ways to improve methods of satisfaction with work motivation, are studied. invited. It should be noted that at the current stage of economic development, the problem of planning employees working in enterprises and organizations, financial incentives and development of labor plays a special role in the country’s economy, along with ensuring the personal interests of employees.